2017
DOI: 10.1038/s41598-017-00053-7
|View full text |Cite
|
Sign up to set email alerts
|

Quadriwave lateral shearing interferometric microscopy with wideband sensitivity enhancement for quantitative phase imaging in real time

Abstract: Real-time quantitative phase imaging has tremendous potential in investigating live biological specimens in vitro.Here we report on a wideband sensitivity-enhanced interferometric microscopy for quantitative phase imaging in real time by employing two quadriwave lateral shearing interferometers based on randomly encoded hybrid gratings with different lateral shears. Theoretical framework to analyze the measurement sensitivity is firstly proposed, from which the optimal lateral shear pair for sensitivity enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…This difference cannot be explained by a difference in the density of dMSNs between the anterior and the posterior striatum. Characterization of the striatum in the Drd1-Cre mice (founder line FK150) yielded similar numbers of Drd1 -positive neurons (1654 ± 92 cells per square millimeter per section in the anterior striatum vs. 1709 ± 127 cells in the posterior striatum; p = 0.529, Wilcoxon rank-sum test), consistent with reports in other Drd1-Cre lines 13 , 14 .…”
Section: Resultssupporting
confidence: 85%
“…This difference cannot be explained by a difference in the density of dMSNs between the anterior and the posterior striatum. Characterization of the striatum in the Drd1-Cre mice (founder line FK150) yielded similar numbers of Drd1 -positive neurons (1654 ± 92 cells per square millimeter per section in the anterior striatum vs. 1709 ± 127 cells in the posterior striatum; p = 0.529, Wilcoxon rank-sum test), consistent with reports in other Drd1-Cre lines 13 , 14 .…”
Section: Resultssupporting
confidence: 85%
“…For example, we found that the hypothalamus/preoptic area, a brain region involved in complex behaviors such as thermoregulation, hunger and sleep, contains cell types with distinct lineage relationships. In particular, analysis of 6 barcodes across 95 cells in ZF1 indicated that there are at least two distinct neural lineages in this region: sst3 + neurons 39 (cluster 27) were clonally related to penkb + neurons 40 (cluster 30), while fezf1 + neurons (cluster 20) and hmx3a + neurons (cluster 28) were clonally related to each other ( Fig. 5c, d ).…”
Section: Resultsmentioning
confidence: 97%
“…Talbot interferometers and their variations, such as multilateral shearing interferometers or modified Hartmann mask interferometers, are widely used at visible [12][13][14][15] and infrared wavelengths [16]. A Talbot interferometer at hard x-rays can use a π-phase shift checkerboard pattern with pitch p as the imaging object.…”
Section: Introductionmentioning
confidence: 99%